Tinnitus treatment clinical protocols - Tyler, Richard S.; Perreau, Ann (Thieme, 2022)
"Since publication of the first edition in 2005, new developments have impacted the treatment paradigm for tinnitus, such as sensory meditation and mindfulness. Tinnitus Treatment: Clinical Protocols, Second Edition, by world-renowned tinnitus experts and distinguished authors Richard S. Tyler and Ann Perreau provides comprehensive background information, up-to-date strategies, essential tools, and online supplementary materials grounded in years of clinical experience and research. It fills a gap in graduate education and available materials to empower audiologists to effectively treat patients suffering from bothersome to severely debilitating symptoms associated with tinnitus or hyperacusis"--